Rights of Rivers: Learning from the River Whanganui Case - Finette Unigbe, Ngozi (Christ University Law Journal, 2022)
Generally, laws meant to protect nature usually suffer setbacks with respect to either their provisions or their mechanisms of enforcement. While certain laws have no enforceable right to a clean environment, others lack sufficient deterrence or require strict proof of causation to ground action. Consequently, suggested reforms include addressing the constitutional challenge of justiciability, improving sanctions, creating compensation guidelines, and amending laws on proof of causation. The enforcement mechanisms of the laws can benefit from strengthening good governance, building the capacity of the judiciary to be able to effectively adjudicate on conservation-related matters, and generally encouraging hybrid enforcement mechanisms.